EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN BIOLOGI : LITERATURE REVIEW - Atip Nurwahyunani; Ipah Budi Minarti, Riska Ayu Nabila, Anggi Septia Pramaista, Ainin Tusamma Salsabila, Bagas Prio Sap (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The aim of this research is to determine the influence of using the Problem Based Learning (PBL) model on Learning Outcomes, Critical Thinking Skills, and Problem- Solving Abilities in students' biology education. The data collection technique used is a literature review method. The method employed in this study is a literature review to analyze the impact of the PBL model. Data is collected through documentation by searching relevant journals on this topic via Google Scholar, covering the past 5 years from 2019 to 2023. Based on the analysis of 10 articles, it is found that the implementation of the PBL learning model has a positive influence on students' 4C skills.